Automation of Watering Systems in Gardens Using Programmable Logic Controller (PLC) - Bayu Dwinugroho, Theofilus; Tri Hapsari, Yaning; Arya Pribadi , Pradipta (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2025)
The background of this research is based on automation, where automation is a technology used to carry out work processes or procedures without human assistance.  In the current era of the industrial revolution 4.0, manual activities that use human labor are starting to decrease and are replaced by automated systems and tools in order to streamline and effectively operate a field of work. Programmable Logic Controller (PLC) can be defined as a microcomputer-based controller that uses programmed in-memory instructions to apply logic, sequencing, timing, counting and arithmetic functions via digital or analog input/output (I/O) modules   , to control the machine and process. This PLC is commonly used in the industrial world as a tool for automation of production machines.  Automation of the watering system in the garden aims to water the garden without using human labor.  The research stage begins with literature study and field observation activities followed by the design  of ladder diagrams on PLCs. The PLC ladder diagram simulation that was then implemented in the field has been carried out and the automation of this garden watering system can run well with a shorter waterng time (15 min) and less water consumption (27.4 lt) and can operate without human intervention.